2019
DOI: 10.3389/fpls.2019.01431
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Understanding the Physiological and Molecular Responses of Sugar Beet to Salt Stress

Abstract: Soil salinity is a major environmental stress on crop growth and productivity. A better understanding of the molecular and physiological mechanisms underlying salt tolerance will facilitate efforts to improve crop performance under salinity. Sugar beet is considered to be a salt-tolerant crop, and it is therefore a good model for studying salt acclimation in crops. Recently, many determinants of salt tolerance and regulatory mechanisms have been studied by using physiological and ‘omics approaches. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 99 publications
1
38
0
Order By: Relevance
“…Sugar beet inherited the salt tolerance trait from its ancestor sea beet (B. vulgaris ssp. Maritima), which grows naturally along the Atlantic coasts of Western Europe (Lv et al, 2019). We consistently found that low concentrations of neutral and alkaline salts stimulated growth.…”
Section: Phenotypic and Physiological Response To Neutral Salt And Almentioning
confidence: 51%
See 1 more Smart Citation
“…Sugar beet inherited the salt tolerance trait from its ancestor sea beet (B. vulgaris ssp. Maritima), which grows naturally along the Atlantic coasts of Western Europe (Lv et al, 2019). We consistently found that low concentrations of neutral and alkaline salts stimulated growth.…”
Section: Phenotypic and Physiological Response To Neutral Salt And Almentioning
confidence: 51%
“…To cope with saline-alkaline stress, plants have evolved a variety of strategies to adapt to the saline-alkali environments. In general, the adaptive strategies of plants to neutral salt stress mainly include accumulating of osmotic adjustment substances, enhancing the reactive oxygen species (ROS) scavenging system and maintaining ion homeostasis (Yang and Guo, 2018b;Lv et al, 2019). Many genes associated with these salt tolerant physiological and biochemical processes were identified through genomics or transcriptomic tools (Prerostova et al, 2017;Geng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The salt tolerance of sugar beet is a complex trait that is determined by many physiological and metabolic pathways, including an increased content of compatible solutes [22]. Lv et al believe that the most important factor for beet salt tolerance may be osmotic adjustment [40].…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of ions (Na + and Cl − ) is toxic to cells by decreasing the water potential and stomatal conductance. At the same time, a low water potential in saline soil makes it difficult for the roots of plants to absorb water, causing physiological drought [3]. However, in order to survive under salt stress, plants adapt a series of complex strategies, including the efflux of ions, increased antioxidant enzyme activity and synthesis of osmotic adjustment proteins to cope with the stress.…”
Section: Introductionmentioning
confidence: 99%